Toxic effects induced by nonylphenol (NP) and ethoxylated nonylphenol (NP-9) in Caenorhabditis elegans (2020)
Needs in the field of cleanliness and asepsis have evolved over time. Among the most widely used chemicals in the world today are emerging pollutants. One of these contaminants is nonylphenol ethoxylate (NP-9), also known as Tergitol, and its degradation product, nonylphenol (NP), active ingredients present in nonionic surfactants used as herbicides, cosmetics, paints, plastics, disinfectants and detergents. These chemicals and their metabolites are commonly found in environmental matrices. The objectives of this research work were: 1. To assess the toxicity of NP and NP-9 in C. elegans. 2. To determine the gene expression profile for different toxicity mechanisms in C. elegans. 3. To determine the intergenerational effects caused by exposure to NP-9 in C. elegans. 4. To identify possible intergenerational neurotoxic effects from exposure to NP-9 in C. elegans. Wild-type L4 larvae were exposed to different concentrations of the surfactants to measure functional endpoints like; lethality, length, width, locomotion and lifespan. Transgenic green fluorescent protein (GFP) strains were employed to estimate changes in relative gene expression and promote the activation of toxicity signaling pathways related to mtl-2, gst-1, gpx-4, gpx-6, sod-4, hsp-70 and hsp-4. Additionally, stress response was also assessed using a daf-16::GFP transgenic strain. RT-qPCR was utilized to measure mRNA expression for neurotoxicity-related genes (unc-30, unc-25, dop-3, dat-1, mgl-1, and eat-4). In the results of the first aim, lethality was concentration dependent, with 24-h LC50 of 122 μM and 3215 μM for NP and NP-9, respectively. Both compounds inhibited nematode growth, although NP was more potent; and at non-lethal concentrations, nematode locomotion was reduced. The increase in the expression of tested genes was significant at 10 μM for NP-9 and 0.001 μM for NP, implying a likely role for the activation of oxidative and cellular stress, as well as metabolism pathways. Except for glutathione peroxidase, which has a bimodal concentration-response curve for NP, typical of endocrine disruption, the other curves for this xenobiotic in the strains evaluated were almost flat for most concentrations, until reaching 50–100 μM, where the effect peaked. NP and NP-9 induced the and nuclear translocation of DAF-16, suggesting that transcription of stress-response genes may be mediated by the insulin/IGF-1 signaling pathway. In contrast, NP-9 induced a concentrationdependent response for the sod-4 hsp-4 mutants, with higher fluorescence induction than NP at similar levels. For the second aim, data were obtained from parent worms (P0) and the first generation (F1). Lethality of the nematode was concentration-dependent, with 48 h-LC50 values of 3215 and 1983 μM in P0 and F1, respectively. Non-lethal concentrations of NP-9 reduced locomotion. Lifespan was also decreased by the xenobiotic, but the negative effect was greater in P0 than in F1. Non-monotonic concentrationresponse curves were observed for body length and width in both generations. The gene expression profile in P0 was different from that registered in F1, although the expression of sod-4, hsp-70, gpx-6 and mtl-2 increased with the surfactant concentration in both generations. None of the tested genes followed a classical concentration-neurotoxicity relationship. In P0, dopamine presented an Inverted-U curve, while GABA and glutamate displayed a bimodal type. However, in F1, inverted U-shaped curves were revealed for these genes. In short, NP and NP-9 affect the physiology of C. elegans and modulate gene expression related to reactive oxygen species (ROS) production, cellular stress and metabolism of xenobiotics. Additionally, the NP-9 isomer induced intergenerational responses in nematode through mechanisms involving ROS, and alterations of the GABA, glutamate, and dopamine pathways.